2007
DOI: 10.1038/sj.onc.1210350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of novel cell cycle inhibitors in mantle cell lymphoma

Abstract: Signature abnormalities in the cell cycle and apoptotic pathway have been identified in mantle cell lymphoma (MCL), affording the opportunity to develop targeted therapies. In this study, we tested a novel class of kinase inhibitors, styryl sulfones, which differ from prior cell cycle inhibitors in that they are not related to purines or pyrimidines. We observed that two closely related compounds, ON013100 and ON01370, altered the growth and cell cycle status of MCL lines and potently inhibited the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In vitro studies with 28 showed that incubation of human leukemic cells with this compound results in the inhibition of PI3K/AKT pathway, down regulation of cyclin D1, induction of NOXA and BIM and activation of JNK pathway. 6 Treatment of MDS patients with 28 results in a dramatic reduction of cytogenetically abnormal cells with a minimal inhibition of normal hematopoiesis. This drug is currently in Phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies with 28 showed that incubation of human leukemic cells with this compound results in the inhibition of PI3K/AKT pathway, down regulation of cyclin D1, induction of NOXA and BIM and activation of JNK pathway. 6 Treatment of MDS patients with 28 results in a dramatic reduction of cytogenetically abnormal cells with a minimal inhibition of normal hematopoiesis. This drug is currently in Phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with 6s, 6aa, and 6ab show that these compounds altered the growth and cell cycle status of mantle cell lymphoma cell lines and potently inhibited the expression of several important proteins, including cyclin-dependent kinase 19,20 4, p53, mouse double minute 2 (MDM2), and cyclin D. 23 Since 6s, 6aa, and 6ab are highly effective in various combinations with conventional chemotherapy, 23 the lack of overt hematotoxicity of these compounds may be beneficial for testing novel combinations for advanced cancers, including tumors resistant to conventional chemotherapy. In addition, their safety profile seen with normal hematopoietic cells suggests that these compounds have a potential use in in vitro purging of tumor cells from patient bone marrow for use in autologous bone marrow transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…1A) [1]. While the drug has little or no effect on normal cell viability, it induces apoptosis, and has activity against most human cancer cell lines in vitro (>100 tumor types tested, including drug resistant lines) as well against a broad spectrum of human xenografts in mice [2]. As a potent mitotic inhibitor the drug also inhibits cyclin D1 expression and induces selective G2/M arrest of tumor cells characterized by spindle abnormalities leading to apoptosis [3].…”
Section: Introductionmentioning
confidence: 99%